2017
DOI: 10.1038/s41418-017-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like 3 is required for melanoma cell survival by maintaining genomic stability

Abstract: Lysyl oxidase-like 3 (LOXL3) is a member of the lysyl oxidase family comprising multifunctional enzymes with depicted roles in extracellular matrix maturation, tumorigenesis, and metastasis. In silico expression analyses followed by experimental validation in a comprehensive cohort of human cell lines revealed a significant upregulation of LOXL3 in human melanoma. We show that LOXL3 silencing impairs cell proliferation and triggers apoptosis in various melanoma cell lines. Further supporting a pro-oncogenic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
1
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 46 publications
7
39
1
12
Order By: Relevance
“…For instance (and as we have previously suggested; (Cebria-Costa et al, 2019), it could protect cells from aberrant activation of the DNA damage response and any consequent cell cycle arrest or cell fate decisions, such as apoptosis or senescence. In fact, another LOX family member, LOXL3, has a major role in the maintenance of genomic stability (Santamaria et al, 2018). We also have demonstrated here that maintenance of this heterochromatin status is required for the ability of TNBC cells to migrate and invade.…”
Section: Discussionsupporting
confidence: 53%
“…For instance (and as we have previously suggested; (Cebria-Costa et al, 2019), it could protect cells from aberrant activation of the DNA damage response and any consequent cell cycle arrest or cell fate decisions, such as apoptosis or senescence. In fact, another LOX family member, LOXL3, has a major role in the maintenance of genomic stability (Santamaria et al, 2018). We also have demonstrated here that maintenance of this heterochromatin status is required for the ability of TNBC cells to migrate and invade.…”
Section: Discussionsupporting
confidence: 53%
“…LOXL3 is a member of the lysyl oxidase family. It is reported that LOXL3 can regulate genome stability and melanoma progression (Santamaria et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, specific phosphorylations or other post translational modifications of acute phase or other common blood proteins might provide some greater utility than increases in these proteins alone [5, 6063]. Many of the proteins that varied in ovarian cancer were previously shown to play a role in cancer biology, or were previously established tumor diagnostic or prognostic markers and several have previously been detected in the plasma of cancer: Coagulation factor XIII has been suggested to be a biomarker for screening colorectal cancer [9]; P4HA1 is a prolyl 4-hydroxylase that may be a prognostic marker for glioma [64]; Glipican has been localized to exosomes and previously implicated as a biomarker of cancer [42]; Laminin B2 promotes non-small cell lung cancer [65]; CSR1 is a tumor suppressor gene that activates CPSF3 preventing the interaction of XIAP with caspase [66]; MORN3 is a testes-cancer antigen that recruits the Sirtuin deacetylase that modifies P53 [67]; SIRT1 (Sirtuin) is a histone deacetylase that may regulate tumor formation [68]; Cyclin 1-like (CCN12) plays a role in cell cycle progression and proliferation [69]; NMI is an N-MYC and STAT interactor shown to increase in protein expression with tumor grade and plays a role in cell cycle progression [70]; Increased ITGB1 integrin beta 1 has been shown to be associated with some, but not all, solid cancers [71]; A gene expression array identified NEFM as indicative of the risk of prostate cancer [72]; PLEC1 was shown to promote esophageal cancer cell progression by maintaining the expression of SNAIL [73]; SRGN was show to be expressed in the exosomes of adenocarcinoma by LC–ESI–MS/MS [74]; DHCR reduces cholesterol, may play a role in cancer [75] and selective and potent inhibitors of DHCR have been developed [76]; SMC5 complexes with MMS21 that acts as an E3 ligase required to avoid gross chromosomal rearrangements [77]; Semaphorins such as SEMA6B were strongly down regulated in breast cancer [78]; Lysyl oxidase-like 3 was required for melanoma cell survival [79]; Seizure related 6 homolog (SEZ6L2) showed increased gene expression in primary lung cancer by RT-PCR and Western blot [80].…”
Section: Discussionmentioning
confidence: 99%